Finite element analysis of secondary effect of midfoot fusions on the spring ligament in the management of adult acquired flatfoot. (June 2020) - Cifuentes-De la Portilla, Christian; Pasapula, Chandra; Larrainzar-Garijo, Ricardo; Bayod, Javier
Abstract: Background: Surgical treatment of adult acquired flatfoot deformity can involve arthrodesis of the midfoot to stabilize the medial column. Few experimental studies have assessed the biomechanical effects of these fusions, because of the difficulty of measuring these parameters in cadavers. Our objective was to quantify the biomechanical stress caused by various types of midfoot arthrodesis on the Spring ligament. To date this is not known. Methods: An innovative finite element model was used to evaluate flatfoot scenarios treated with various combinations of midfoot arthrodesis. All the bones, cartilages and tissues related to adult acquired flatfoot deformity were included, respecting their biomechanical characteristics. The stress changes on the Spring ligament were quantified. Both foot arch lengthening and falling were measured for each of the midfoot arthrodeses evaluated. Findings: Arthrodesis performed for stabilization of the talonavicular joint leads to a higher decrease in stress on the Spring ligament. Talonavicular fusion generated a Spring ligament stress decrease of about 61% with respect to the reference case (without any fusion). However, fusing the naviculocuneiform joints leads to an increase in the stress on the Spring ligament. Interpretation: This important finding has been unknown to date. We advocate caution regarding fusion of the naviculocuneiform joint as it leads to increased stresses across the Spring ligament and therefore accelerates the development of planovalgus. Highlights: Various combinations of midfoot arthrodeses were evaluated in flatfoot scenarios. Stress in spring ligament was analyzed in some midfoot arthrodeses scenarios. Both foot arch lengthening and fall were measured for all the arthrodeses cases. Naviculocuneiform arthrodesis notably increases the spring ligament stress Talonavicular arthrodesis leads to decrease the spring ligament stress.